Foot clearance measurement - Lee, Jonavan Zisheng (2014)
Walking is the most primitive form of gait locomotion innate to humans. It can be considered as one of the most important ability of man, since it guarantees mobility and independence, and therefore social integration and freedom. There are various patterns, postures and strategies employed by humans in achieving locomotion and thus there is no “one fixed way” of executing this kinematic-ally complex motion called gait. The way a person executes this motion of walking will determine whether the person moves forward in the intended direction of travel or whether the person will fall down. And falls can cause the faller to graze a knee, fracture a toe, become paralyzed or it may even cause death to the faller. So, if a person’s gait pattern can be studied, quantified and predicted, that means a fall could also possibly be predicted and prevented. This could go a long way in aiding older adults and people who have mobility impairments. In light of all these, the study and research of the human gait and its related applications such as fall detection systems and many other gait-related projects have increased dramatically. Foot clearance, which is defined as the foot’s height during the swing phase , is just one aspect in gait studies. In this project, foot clearance is measured using the US-100 ultrasonic sensor module that is temperature-compensated. It is interfaced with the CC2430 board by Texas Instruments. It is a 2.4GHz radio frequency (RF) transceiver board used primarily for it wireless RF communications functionality. Benchmarking, static and dynamic tests were carried out on this ultrasound transceiver system and the results and conclusions on foot clearance measurements were made.